2006
DOI: 10.1029/2006jb004321
|View full text |Cite
|
Sign up to set email alerts
|

Upper mantle structure of southern Africa from Rayleigh wave tomography

Abstract: [1] Rayleigh wave phase velocities in southern Africa have been obtained at 18 periods from 20 to 167 s using a two-plane wave method. These phase velocities are utilized in subsequent inversions to solve for shear wave structure in the crust and upper mantle of southern Africa. A fast lithosphere lid is imaged beneath most parts of southern Africa. The lid thickness is estimated on the basis of the variation of shear wave velocity with depth and ranges from $80 km beneath the Namaqua-Natal belt to 180 ± 20 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
139
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(165 citation statements)
references
References 63 publications
24
139
2
Order By: Relevance
“…Jun Korenaga is thanked for providing a preprint of a paper containing new analyses of olivine creep parameters. (Li and Burke, 2006) > 150 km (Chen et al, 2007) Consistent with 250 km (Bruneton et al, 2004a) S-Receiver function~ 250-300 km (Kumar et al, 2007) Magnetotelluric (MT) 230 km (Miensopust et al, 2006) 210 km at LdG 260 km average (Jones et al, 2003) 205 km at NAT (Jones, 1999) > 300 km (Korja, 2007) . The LAB may also correlate with a downward extinction of seismic anisotropy (e.g., Gaherty and Jordan, 1995) or a change in the direction of anisotropy (e.g., Debayle and Kennett, 2000a;2000b;Sebai et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jun Korenaga is thanked for providing a preprint of a paper containing new analyses of olivine creep parameters. (Li and Burke, 2006) > 150 km (Chen et al, 2007) Consistent with 250 km (Bruneton et al, 2004a) S-Receiver function~ 250-300 km (Kumar et al, 2007) Magnetotelluric (MT) 230 km (Miensopust et al, 2006) 210 km at LdG 260 km average (Jones et al, 2003) 205 km at NAT (Jones, 1999) > 300 km (Korja, 2007) . The LAB may also correlate with a downward extinction of seismic anisotropy (e.g., Gaherty and Jordan, 1995) or a change in the direction of anisotropy (e.g., Debayle and Kennett, 2000a;2000b;Sebai et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…• absolute velocity variation with depth -taking a specific V s value instead of a percent velocity anomaly as a proxy (Li and Burke, 2006);…”
Section: Defining the Lab Using Surface-wave Observationsmentioning
confidence: 99%
“…5b). Most models do not fit neither our, nor the xenolith-based isotropic S wave velocity profiles of James et al (2004), but there is a fit with the DataX model of Larson et al (2006) and, in to lesser extent, with the model L&B06 of Li and Burke (2006). The QPM model of Qiu et al (1996) and the model of Hansen et al (2009) (H09) display a marked decrease of V s at 110-120 km that is not observed in the xenolith data.…”
Section: Comparison With Seismological Velocity Profiles and Tomograpmentioning
confidence: 90%
“…on top of a low velocity layer (Jordan, 1978;Priestley, 1999;James et al, 2001;Li and Burke, 2006;Priestley et al, 2006). Most body and surface wave tomography models indicate that this lid is 200-250 km thick beneath the Kaapvaal craton (James et al, 2001;Chevrot and Zhao, 2007;Fishwick, 2010).…”
Section: Baptiste and A Tommasi: Seismic Properties Of The Kaapvamentioning
confidence: 99%
“…In general, shear-wave velocity structure can provide better rheological images than that of the P-wave tomography, and surface-wave phase velocity is sensitive to the variation of shear-wave velocity, thus, surface-wave tomography is one of the most important tools to understand the rheological and tectonic structures in the crust and the upper mantle (Li and Burke 2006;Jia and Zhang 2008;Ding et al 2008;Jobert et al 1985;Toksoz and Anderson 1966;Kanamori 1970;Forsyth 1975;Zhang and Lay 1996;Zhang and Ma 1997). A number of studies have resolved the crustal and upper-mantle velocity structures using longperiod surface-wave data Yanovskaya and Kozhevnikov 2003;Huang et al 2003;He et al 2002He et al , 2009).…”
mentioning
confidence: 99%